A novel Bluetongue virus serotype 3 strain in Tunisia, November 2016. Issue 3 (15th March 2017) - Sghaier, S.; Lorusso, A.; Portanti, O.; Marcacci, M.; Orsini, M.; Barbria, M. E.; Mahmoud, A. S.; Hammami, S.; Petrini, A.; Savini, G.
Summary: Since 1998, southern Europe has experienced multiple incursions of different serotypes and topotypes of Bluetongue virus, a vector‐borne transmitted virus, the causative agent of Bluetongue (BT), a major disease of ruminants. Some of these incursions originated from northern Africa, likely because of wind‐blown dissemination of infected midges. In this report, we describe the detection and whole genome characterization of a novel BTV‐3 strain identified in a symptomatic sheep in Tunisia. Sequences were immediately deposited with the GenBank Database under Accession Nos KY432369‐KY432378. Alert and preparedness are requested to face the next vector seasons in northern Africa and the potential incursion of this novel strain in southern Europe.